(untitled) (Progressive Agriculture, 2014)
Computer based image processing system has been developed to automatically calculate the damaged area and also to identify the location of disease infected area of rice leaves. The developed image processing system separates the infected regions on leaf by pixel-wise processing. The color intensities associated with image pixels are used as inputs, which are taken by the software and produce the desired output. Experimental results show that the proposed system can produce accurate results in every case whereas conventional eye-estimation technique is not accurate. The amount of damaged area, as identified by proposed software system, can potentially be used in many decision making processes, like determination of the amount of pesticides need to be sprayed in a field. Moreover, an automated machine can be combined with this software to eliminate the requirement of human operators. Also this system may eliminate the requirement of costly Leaf Area Meter. DOI: http://dx.doi.org/10.3329/pa.v18i2.18210 Progress. Agric. 18(2): 209 - 213, 2007